Potentials of ethanolic extracts oe (jatropha curcas) on the gut morphology of broilers (2014)
In a study conducted to evaluate the effect of Jatropha curcas leaf extract on the gut morphology of broiler chickens, one hundred and fifty day old Arbor Acre broiler chicks were randomly allocated to five treatments, each replicated five times, with six birds per replicate over a period of forty two days. The birds were allocated to the following treatments (T): T1 (Negative control, no antibiotics), T2 (positive control, with antibiotics), T3 (0.25g/100kg Jatropha curcas leaf extract), T4 (0.50g/100kg J. curcas leaf extract) and T5 (0.75g/100kg J. curcas leaf extract). Samples were collected from the ileum and duodenum for gut morphology assay, with the results of gut morphology revealing that J. curcas supplementation improved villi height in duodenum (p<0.05), while significantly decreasing values for villi height in the ileum (p<0.05). Crypt depth values were also significantly influenced by inclusion of antibiotics and 0.25% J. curcas extract.